Global model of an atmospheric-pressure capacitive discharge in helium with air impurities from 100 to 10000 ppm - Bowen Sun; Ding-Xin Liu; Felipe Iza; Sui Wang; Aijun Yang; Zhijie Liu; Ming-Zhe Rong; Xiao-Hua Wang (2019)
Helium is a common working gas for cold atmospheric plasmas (CAPs) and this is often mixed with other gases, such as oxygen and nitrogen, to increase its reactivity. Air is often found in these plasmas and it can be either introduced deliberately as a precursor or entrapped in systems that operate in open atmosphere. In either case, the presence of small traces of air can cause a profound change on the composition of the plasma and consequently its application efficacy. In this paper, a global model for He+Air CAPs is developed, in which 59 species and 866 volume reactions are incorporated, and a new boundary condition is used for the mass transport at the interface between the plasma and its surrounding air gas. The densities of reactive species and the power dissipation characteristics are obtained as a function of air concentrations spanning from 100 to 10000 ppm. As the air concentration increases, the dominant cation changes from O2 + to NO+ and then to NO2 + , the dominant anion changes from O2 - to NO2 - and then to NO3 - , the dominant ground state reactive oxygen species changes from O to O3, and the dominant ground state reactive nitrogen species changes from NO to HNO2. O2(a) is the most abundant metastable species and its density is orders of magnitude larger than other metastable species for all air concentrations considered in the study. Ion Joule heating is found important due to the electronegative nature of the plasma, which leads to the fast decrease of electron density when the air concentration is larger than 1000 ppm. The generation and loss pathways of important biologically relevant reactive species such as O, O2 - , O3, OH, H2O2, NO, HNO2, HNO3 are discussed and differences with the pathways observed in He+O2, He+H2O, Ar+Air and pure air plasmas are highlighted. Based on the simulation results, a simplified chemistry set with 47 species and 109 volume reactions is proposed. This simplified model greatly reduces the computational load while maintaining the accuracy of the simulation results within a factor of 2. The simplified chemistry model is computationally much less intensive, facilitating its integration into multidimensional fluid models for the study of the spatio-temporal evolution of He+Air CAPs.